Nivolumab adjuvant therapy for esophageal cancer: a review based on subgroup analysis of CheckMate 577 trial - Lin, Yan; Liang, Huan-Wei; Liu, Yang; Pan, Xin-Bin (Frontiers in Immunology, 2023)
Esophageal cancer is the sixth most common cancer worldwide. Approximately 50% of patients have locally advanced disease. The CROSS and NEOCRTEC5010 trials have demonstrated that neoadjuvant chemoradiotherapy followed by surgery is the standard treatment for patients with resectable disease. However, a pathological complete response is frequently not achieved, and most patients have a poor prognosis.The CheckMate 577 trial demonstrates that nivolumab adjuvant therapy improves disease-free survival in patents without a pathological complete response. However, there are still numerous clinical questions of concern that remain controversial based on the results of the subgroup analysis. In this review, we aim to offer constructive suggestions addressing the clinical concerns raised in the CheckMate 577 trial.